Structural productive and management traits in two Mediterranean large-scale grazing systems - Salis L.; Sitzia M.; Bagella S.; Marrosu M.; Roggero P.P. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The aim of this study was to analyse structural, productive and pasture traits of dairy sheep (DS) and beef cattle (BC) grazing systems of a cork oak silvo-pastoral area located in NE Sardinia. In 2009, farm and flock size, secondary grasslands/crops land, animal feed and production, crop management of three DS and two BC farms were compared. Eleven fenced pastures were assessed for their herbage mass production (Hm), grazing value (GV), species richness and stocking rate (SR). DS and BC showed a low-input management related to the high incidence of secondary grassland (>80% of total land). Feed from pasture grazing, on average, supplied more than 70% of the total animal energy requirements for both DS and BC. Mineral fertilizer was distributed at low rate, only in the cultivated hay and forage crops which are grown on arable land to improve the grassland pasture. DS pasture showed a higher Hm than BC pasture, both in spring and autumn, and a significantly higher level of SR. The vegetation analysis did not reveal differences between DS and BC pasture in terms of GV and species richness that were relatively high. Subterranean-clover was the most relevant species in the secondary grasslands.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)